An analysis of teaching character education technique and values found in ‘Confession” directed by Tetsuya Nakashima - Cynantia Rachmijati (Journal of Advanced Multidisciplinary Research, 2020)
“Confession” is a Japanese thriller drama movie about a teacher named Yuko Moriguchi who lost her daughter where she believed that some of her students involved in her daughter’s death. The objectives of this research are (1) to explain character education teaching technique (2) to explain the character education values found in the “Confession movie”.  This research is descriptive qualitative by content analysis. The data source was taken from scene in the “Confession” movie. The object of this research is movie “Confession” directed by Tetsuya Nakashima with 106 minutes running time. The research data are in the form of speech, behaviour, context displayed by the characters through visualization in the film. And analysed based on character education principals teaching and character educational values proposed by Ministry of National Education (2010). The researcher finds 16 data, include 5 data of character education teaching techniques and 11 data of values. Therefore it can be concluded that the character education teaching technique based on this movie are : promoting basic values and explained to the students what makes a good person, be friends with the students and understand their characters, be close to them and talk to them as friends, believe in them and always motivate, praise and encourage them. Whereas the characters values found are: honesty, tolerance, discipline, hard-working, creative, democratic, patriotic, appreciative, peace-loving and social care. It is also noted that movie can be used as aid in teaching character education where it can be obtained through themes, messages, and advice in the values of the movie storyline.